A New Biological System For Detecting Environmetal Carcinogens And /Or Mutagenes And Their Adversary - Mohammed, B. M.A; Katy, N.Sh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new test system for detecting environment carcinogenes and/or mutagenes and their adversary It has been induced. One hundred and fifty mutants were isolated from the basidiomycete fungus Coprinus cinereus which were resistant to guanine analogue S- az.aguanine .All the spontaneous and induced with UV light origin mutants were isolated from the wild type strains Bc9/6.6 and Hd5.5 .These mutants were te ted on selective medium containing different concentrations of the analogue and also to their ability to usc purine bases and their degredated products as a sole nitrogene source were tested ; and their ability to grow on HAT medium was tested . According to the results obtained from these test; mutants were classified into four phenotypic groups for each iJd -type strain . All the 8-az.aguanine resistant mutants were d.ikaryotized with compatible wild strains. The dikaryons produced were unable to grow on medium containing 8-az.aguanine which establish the recessiveness of the mutations to their respective wi ld-type alleles. Complementation test detcrmind four genes which controll the resi stance to 8- azaguaninc in Coprinus cincres .These genes were desi gnated azg-1, azg-2, azg’-3, azg-4.Three of these genes azg-1, azg-2 and azg’-4werc carried by Bc9/6.6 and Hl /5.5 mutants. While, azg-3 gene was found in Bc9/6.6 mutants only. These genes are determ.ind for the first time in fungus coprinus cinereus . Mutants which carry azg-1 gene were characterized by their inability to use hypozanthine and guanine as a sole nitrogen source in the medium ; their failure to grow on HAT medium and their resistance to all concentrations of 8- az.aguanine used.This gene is considered to IBN AL- HAITHAM J.FOH PURE & API’L.SCI. VOL.19(4) 2006 represent a mutation led to lose or modify the specificity of the enzyme hypoxauthine -guanine phosphoribosyl transferase (HGPRT) whi ch play an important role in transferring hypoxauthine and guanine to their nucleotides by salvage pathway. Spore analysis indi cated that azg’-1 gene locted in linkage group II ,since it gave a distance of 28 map units with the mating type gene B. The assessment of the cytotoxic , mutagn ic and antimutagcâ€¢tic role of the aqueous extract of garl ic (Allium sativum L.) against the genotoxic effect of mitomycin - C ( MMC ) evaluate the ability of the mutagen to induce mutation in HGPRT gene by using the asexual spores (oidia )of Copninus cineraus for the strain AZG78 and by depending on the viabil ity and mutation rate in HGPRT gene test .To assess cytotoxity and mutagenecity of garlic extract , gradual concentrations were prepared . The concentration of choice was considered with respect to two factors ; high survi val rate and low mutagenic activity (similar to negative control ). To examine the antimutagenic effects of the extract, an interation was made between the crude extract and the mutagen MMC with respect to three kinds of treatments before , aOer and with mutagen . The study concentrated on two sides 1- on the toxic and /or m utagenic effect of the aqueous extract of garlic . 2 - Antimutagenic activity of the extract with respect to the mutageen MMC . However, this activity was dependent on the type of the treatment . The extract showed best antimutagenic activity when it was used before the mutagen , so itis considered as desmutagen to the genotox i c effects of MMC. These data support the hypothesis that garlic compounds may be eflicacius in preventions of cancer and also we could use the HGPRT gene as a sensitive biological system in detecting environmental mutagenes or carcinogens and their adversary .